ANALISIS PERBEDAAN KEPUASAN PASIEN TERHADAP ASUHAN KEPERAWATAN ANTARA METODE FUNGSIONAL DAN ALOKASI PASIEN DI RUMAH SAKIT ISLAM SURAKARTA - Hastono, Heru Puji; Pratiwi, Arum (Jurnal Berita Ilmu Keperawatan, 2009)
Patient satisfaction is one factor which has big role in hospital services. Nurses as one employees who work in hospital must work more to establish its satisfaction especially in hospital . In Nursing application area, nurses are independent to practice each methods of Nursing Professional Delivery. Two method which widely used in nursing practice especially in Surakarta Islamic Hospital is Functional method and Allocation of patient/nursing method It was interesting to compare those two method and how those method influence in patient satisfaction. The Research before in the same hospital has reported that there was no difference between Team Method and Functional method. Method This Research represent the quantitative comparative research, non experiment. While research device used cross sectional. The population in this research, all patient who admitted in Surakarta Islamic Hospital and receive one of two method. Sample counted 60 patients. Analyze the data used Independent t test. Conclusion. Results of research shown: (1) Majority of sample were in productive period, educational background is high school and bachelor stage, and most of them are private worker. (2) There was no difference in patient satisfaction between two methods (3) Two groups declare that they were satisfaction with those method while they were admitted.